0
$\begingroup$

I've been trying to prove that if $X_n \rightarrow X$ in distribution, that is for $F_n, F$ - distribution functions of $X_n, \ X$ resp we have:

$$\forall x: \ F \ \text{is continuous in} \ x : \ \Rightarrow F_n(x) \rightarrow F(x) \ \ \ (n \rightarrow \infty) \ \ \ \ \ \ \ (*)$$

then also $aX_n + b \rightarrow aX+b$ in distribution.

I've tried using:

$1)$ A sequence of distributions converges weakly $P_n \rightarrow P$ by definition, if the sequence of their distribution functions satisfies $(*)$

And it is equivalent to: for any bounded continuous function $f: \mathbb{R} \rightarrow \mathbb{R}$ we have $\int_{\mathbb{R}} f dP_n \rightarrow \int_{\mathbb{R}} f dP \ \ \ (n \rightarrow \infty)$

2) By Portmanteau lemma we have $E(f(X_n)) \rightarrow E(f(X)) \ \ \ \ (n \rightarrow \infty)$

But neither has lead me anywhere so far.

Could you help me out a bit?

Thank you!

$\endgroup$
1
$\begingroup$

By Portmanteau's lemma, it suffices to show

$$\mathbb{E}g(a X_n+b) \to \mathbb{E}g(aX+b) \tag{1}$$

for any continuous bounded function $g$. Since

$$f(x) := g(ax+b)$$

is also a continuous bounded function, this is equivalent to

$$\mathbb{E}f(X_n) \to \mathbb{E}f(X). \tag{2}$$

Can you take it from here?

$\endgroup$
  • $\begingroup$ If $a, b \in \mathbb{R}$, then $E(aX_n+b) = aE(X_n)+b$. And $X_n \rightarrow X$ in distr., $ \iff E(X_n) \rightarrow E(X)$ by Portmanteau lemma. $\endgroup$ – Bilbo Mar 8 '15 at 13:01
  • 1
    $\begingroup$ $X_n \rightarrow X$ in distribution $\iff$ for any $f, E(f(X_n)) ... $ (in particular for $f(x)= g(ax+b)$) $ \ \ \Rightarrow$ $E(g(aX_n +b)) \rightarrow E(g(aX+b)) \ \iff aX_n +b \rightarrow aX+b$, by the lemma $\endgroup$ – Bilbo Mar 8 '15 at 13:11
  • 1
    $\begingroup$ @Bilbo Yes, it is still true, but the proof is more difficult. See this question: math.stackexchange.com/q/317706 $\endgroup$ – saz Mar 8 '15 at 13:21
  • 1
    $\begingroup$ @Bilbo Yes, I was referring to "coinciding". "$c_n X_n'$ coincides wich $c_n X_n$ in distribution" means simply that for each fixed $n \in \mathbb{N}$, we have $c_n X_n = c_n X_n'$ in distribution. $\endgroup$ – saz Mar 8 '15 at 14:06
  • 1
    $\begingroup$ @Bilbo Well, I guess you mean the right thing: $$P_n(c_n X_n \in B) = P_n (c_n X_n' \in B)$$ for any Borel set $B$. (It does not suffice to have equality for $B$ of the form $B=\{x\}$.) $\endgroup$ – saz Mar 8 '15 at 14:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.